ANALISIS POTENSI DEBIT DI BENDUNGAN JUWERO UNTUK PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO - Novangga Wicaksana (FT TE 16 UMY 025, 2016)
Micro Hydro Power (MHP) is a small-scale power plants that use hydropower as the energy of motion . This type of plant does not require a lot of land to build the installation as well as equipment used is relatively simple and easy . The investment cost for the construction is relatively small and stable profits . Keywords: MHP, Investment Cost, Profit